B lymphocytes expressing high levels of PD-L1 are key regulators of diabetes development in non-obese diabetic mice. (October 2019) - Chen, Kun; Xue, Qian; Liu, Fangfang; Liu, Ling; Yu, Caiyong; Bian, Ganlan; Zhang, Kun; Fang, Chao; Song, Jun; Ju, Gong; Wang, Jian
Highlights: Generation of transgenic mice with high PD-L1 expression on a NOD background. NOD.PD-L1Tg mice are resistant to development of diabetes. CD62L − CD44 + CD4 + T cells were decreased in NOD PD-L1 Tg mice. B PD-L1 cells suppress activation of CD4 + T cells and delay onset of diabetes after adoptive transfer of diabetic T cells. Abstract: Programmed cell death 1 ligand 1 (PD-L1) plays a critical role in mediating autoimmune diseases, including type I diabetes (T1D). B cells are important antigen-presenting cells (APCs) that make a major contribution to T1D development. However, B cells expressing low levels of PD-L1 that infiltrate insulitic islets in NOD mice may not inhibit effector T cells and prevent T1D. Here, we generated PD-L1 transgenic NOD (NOD.PD-L1Tg) mice, in which most immune cells overexpress PD-L1, to investigate the ability of B cells overexpressing PD-L1 to inhibit diabetic CD4 + T cells and prevent T1D. The severity of insulitis in NOD.PD-L1Tg mice was significantly lower than in NOD mice and none developed diabetes. In addition, there were no differences in expression of activity markers by APCs following LPS stimulation between two groups. In vitro studies revealed that B cells expressing high levels of PD-L1 inhibited proliferation of and cytokine secretion by pre-diabetic CD4 + T cells, whereas in vivo studies showed that NOD/SCID mice receiving diabetic CD4 + T cells mixed with B cells overexpressing PD-L1 became diabetic at a slower rate. Thus, we propose that B cells showing high expression of PD-L1 protect NOD mice against T1D and downregulate diabetogenic CD4 + T cells.